Market surveillance: foreign experience and approaches to reform in Ukraine - Dyatlova, Valentyna (Skhid, 2013)
In the article examines the international experience in organization and legal support market surveillance, the current status and approaches to reform this sector in Ukraine in accordance with WTO requirements and EU, measures to improve it are founded.